A context-aware concept evaluation approach based on user experiences for smart product-service systems design iteration. (October 2021) - Wang, Zuoxu; Chen, Chun-Hsien; Li, Xinyu; Zheng, Pai; Khoo, Li Pheng
Abstract: With the trend of 'digitalization' and 'servitization' in the manufacturing industry, numerous product-service systems fail to seize a market share and encounter an imbalance between digital investments and expected revenues. This phenomenon is probably caused by the insufficient evaluation on user experience and by the lag between user requirement changes and the offered solutions. Both limitations can be mitigated via automatic Smart PSS evaluation based on broader concerns on user experience information that was collected from either product-service bundles or user behavior. In this paper, a context-aware concept evaluation approach is proposed for Smart PSS design iteration, aiming to satisfy users in a more timely and automatic manner. Derived from the conventional information axiom method, the proposed approach introduces a context-aware evaluation indicator identification module and an automatic system range identification procedure based on natural language processing techniques, and eventually return the most robust concepts during the usage phase. With less human intervention in the design process, it relieves the lag between user requirement changes and the solutions, and reduces the prescriptive instructions in the conventional information axiom method. A case study of a 3D printer company's design iteration is conducted, which proves the proposed approach's feasibility. It is hoped that this work provides practical guidance for achieving a more context-aware Smart PSS development.